Control of a nonanthropomorphic exoskeleton for multi-joint assistance by contact force generation. (15th June 2018) - Lee, Hosang; Kim, Hyung Joo; Park, Jaeheung
In this article, a novel controller for a nonanthropomorphic exoskeleton robot was designed to reduce joint torque of its operator using the contact force between them. Since the joints of the nonanthropomorphic exoskeletons are not directly connected to those of the operator due to the difference between their kinematic structure, joint assistance is performed by transmitting the contact force on their coupling parts instead of transmitting the joint torque of the nonanthropomorphic exoskeleton directly into the human joint. Most of the previous studies have focused on reducing the measured contact force by moving the coupling parts or commanding the robot joint torque. On the contrary, the proposed method focuses on reducing the human joint torque, which is estimated by formulating inverse dynamics, by obtaining possible contact force solutions. The commanding torque of the nonanthropomorphic exoskeleton was calculated by inverse dynamics based on the model information. To verify the control performance of the proposed method, we have developed a simulation environment for a lower-limb nonanthropomorphic exoskeleton. When the coupling part was implemented to be rigid for an ideal case, the joint torque of the human model to perform the same motion was successfully reduced by the given torque reduction ratio. For a more realistic condition, a nonrigid coupling was also implemented as a virtual spring-damper system, and its effect on the control performance was demonstrated in the simulation.